The FES Gene at the 15q26 Coronary-Artery-Disease Locus Inhibits Atherosclerosis. Issue 12 (2nd November 2022) - Karamanavi, Elisavet; McVey, David G.; van der Laan, Sander W.; Stanczyk, Paulina J.; Morris, Gavin E.; Wang, Yifan; Yang, Wei; Chan, Kenneth; Poston, Robin N.; Luo, Jun; Zhou, Xinmiao; Gong, Peng; et al.
Abstract : Background: Genome-wide association studies have discovered a link between genetic variants on human chromosome 15q26.1 and increased coronary artery disease (CAD) susceptibility; however, the underlying pathobiological mechanism is unclear. This genetic locus contains the FES (FES proto-oncogene, tyrosine kinase) gene encoding a cytoplasmic protein-tyrosine kinase involved in the regulation of cell behavior. We investigated the effect of the 15q26.1 variants on FES expression and whether FES plays a role in atherosclerosis. Methods and Results: Analyses of isogenic monocytic cell lines generated by CRISPR (clustered regularly interspaced short palindromic repeats)-mediated genome editing showed that monocytes with an engineered 15q26.1 CAD risk genotype had reduced FES expression. Small-interfering-RNA-mediated knockdown of FES promoted migration of monocytes and vascular smooth muscle cells. A phosphoproteomics analysis showed that FES knockdown altered phosphorylation of a number of proteins known to regulate cell migration. Single-cell RNA-sequencing revealed that in human atherosclerotic plaques, cells that expressed FES were predominately monocytes/macrophages, although several other cell types including smooth muscle cells also expressed FES . There was an association between the 15q26.1 CAD risk genotype and greater numbers of monocytes/macrophage in human atherosclerotic plaques. An animal model study demonstrated that Fes knockout increased atherosclerotic plaque size and within-plaque content of monocytes/macrophages and smooth muscle cells, in apolipoprotein E-deficient mice fed a high fat diet. Conclusions: We provide substantial evidence that the CAD risk variants at the 15q26.1 locus reduce FES expression in monocytes and that FES depletion results in larger atherosclerotic plaques with more monocytes/macrophages and smooth muscle cells. This study is the first demonstration that FES plays a protective role against atherosclerosis and suggests that enhancing FES activity could be a potentially novel therapeutic approach for CAD intervention.